2020
DOI: 10.3389/fbioe.2020.00816
|View full text |Cite
|
Sign up to set email alerts
|

Modular Orthopaedic Tissue Engineering With Implantable Microcarriers and Canine Adipose-Derived Mesenchymal Stromal Cells

Abstract: Mesenchymal stromal cells (MSC) hold significant potential for tissue engineering applications. Modular tissue engineering involves the use of cellularized “building blocks” that can be assembled via a bottom-up approach into larger tissue-like constructs. This approach emulates more closely the complexity associated hierarchical tissues compared with conventional top-down tissue engineering strategies. The current study describes the combination of biodegradable porous poly(DL-lactide-co-glycolide) (PLGA) TIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Aggregation of the biodegradable microparticles leading to the formation of larger objects could be realized using either chemical/physical interactions of microparticle surfaces or via interactions through cells seeded onto the microparticles [ 106 ]. The second approach is more interesting and consists of two stages, when (1) the microparticles used for cell expansion have their surface covered by cells, and (2) cell culture continues at milder conditions to promote cell-cell interactions [ 107 ]. This strategy of microparticle application needs significant control over MPs surface characteristics [ 108 ] and culture conditions [ 107 ].…”
Section: Fabrication and Modification Of Polymeric-based Microparticl...mentioning
confidence: 99%
See 3 more Smart Citations
“…Aggregation of the biodegradable microparticles leading to the formation of larger objects could be realized using either chemical/physical interactions of microparticle surfaces or via interactions through cells seeded onto the microparticles [ 106 ]. The second approach is more interesting and consists of two stages, when (1) the microparticles used for cell expansion have their surface covered by cells, and (2) cell culture continues at milder conditions to promote cell-cell interactions [ 107 ]. This strategy of microparticle application needs significant control over MPs surface characteristics [ 108 ] and culture conditions [ 107 ].…”
Section: Fabrication and Modification Of Polymeric-based Microparticl...mentioning
confidence: 99%
“…The second approach is more interesting and consists of two stages, when (1) the microparticles used for cell expansion have their surface covered by cells, and (2) cell culture continues at milder conditions to promote cell-cell interactions [ 107 ]. This strategy of microparticle application needs significant control over MPs surface characteristics [ 108 ] and culture conditions [ 107 ]. Aggregation of the cell-laden microparticles could be carried out in vitro with an aim to form complex tissue/organ for further implantation, or cell-seeded microparticles could be firstly injected into the targeted tissue and agglomerate in situ by the action of the cells [ 109 ].…”
Section: Fabrication and Modification Of Polymeric-based Microparticl...mentioning
confidence: 99%
See 2 more Smart Citations
“…Biomaterials Science size, with fixed overall porosity and pore size Moreover, the of Entezari et al, 67 who demonstrated possibility of using weak biomaterials in modular scaffolds for repairing large bone defects, with only few percent of strain being sufficient to promote osteogenesis, supports our proposed use of the present scaffold for the repair of non and load-bearing tissues. The bioabsorbable scaffold developed here can also be used in bottom-up tissue engineering strategies, 54,68 culturing different cell types on different fabric layers, which assembled could better mimic the native tissue environment and improve tissue healing. Even though some scaffold requirements are specific to each tissue and a single scaffold design is unlikely to meet the requirements of all human tissues; we propose bioabsorbable warp-knitted spacer fabrics as versatile platform for scaffold manufacturing.…”
Section: Papermentioning
confidence: 99%